2003
DOI: 10.1099/mic.0.26432-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis spoVIF (yjcC) gene, involved in coat assembly and spore resistance

Abstract: In systematic screening four sporulation-specific genes, yjcA, yjcB, yjcZ and yjcC, of unknown function were found in Bacillus subtilis. These genes are located just upstream of the cotVWXYZ gene cluster oriented in the opposite direction. Northern blot analysis showed that yjcA was transcribed by the SigE RNA polymerase beginning 2 h (t 2 ) after the onset of sporulation, and yjcB, yjcZ and yjcC were transcribed by the SigK RNA polymerase beginning at t 4 of sporulation. The transcription of yjcZ was dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…The TF35 strain that harbors gerE :: cat has been described in Kuwana et al (2003). The gerE disruption causes a defect in spore coat formation and makes the spore sensitive to lysozyme as described by Moir (1981).…”
Section: Methodsmentioning
confidence: 99%
“…The TF35 strain that harbors gerE :: cat has been described in Kuwana et al (2003). The gerE disruption causes a defect in spore coat formation and makes the spore sensitive to lysozyme as described by Moir (1981).…”
Section: Methodsmentioning
confidence: 99%
“…3, spoVIF expression was significantly lower in the gerR mutant than in the congenic wild-type strain. These results indicate that while GerR does not control the expression of gerE, it positively controls the expression of spoVIF whose product regulates the level of GerE accumulation in the mother cell (10,11). On the basis of these results, we conclude that GerR acts indirectly on GerE and that its role on at least some of the GerR-controlled cot genes could be indirect and mediated by GerE.…”
Section: Resultsmentioning
confidence: 56%
“…It has been previously reported that GerE fails to accumulate in the sporulating cells of a strain carrying a null mutation in the spoVIF gene (10,11). Since GerE is normally synthesized in the spoVIF mutant, a positive posttranslational effect of SpoVIF on GerE has been proposed (10,11).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations